Nano-sized metabolic precursors for heterogeneous tumor-targeting strategy using bioorthogonal click chemistry in vivo. (December 2017) - Lee, Sangmin; Jung, Seulhee; Koo, Heebeom; Na, Jin Hee; Yoon, Hong Yeol; Shim, Man Kyu; Park, Jooho; Kim, Jong-Ho; Lee, Seulki; Pomper, Martin G.; Kwon, Ick Chan; Ahn, Cheol-Hee; et al.
Abstract: Herein, we developed nano-sized metabolic precursors (Nano-MPs) for new tumor-targeting strategy to overcome the intrinsic limitations of biological ligands such as the limited number of biological receptors and the heterogeneity in tumor tissues. We conjugated the azide group-containing metabolic precursors, triacetylated N -azidoacetyl- d -mannosamine to generation 4 poly(amidoamine) dendrimer backbone. The nano-sized dendrimer of Nano-MPs could generate azide groups on the surface of tumor cells homogeneously regardless of cell types via metabolic glycoengineering. Importantly, these exogenously generated 'artificial chemical receptors' containing azide groups could be used for bioorthogonal click chemistry, regardless of phenotypes of different tumor cells. Furthermore, in tumor-bearing mice models, Nano-MPs could be mainly localized at the target tumor tissues by the enhanced permeation and retention (EPR) effect, and they successfully generated azide groups on tumor cells in vivo after an intravenous injection. Finally, we showed that these azide groups on tumor tissues could be used as 'artificial chemical receptors' that were conjugated to bioorthogonal chemical group-containing liposomes via in vivo click chemistry in heterogeneous tumor-bearing mice. Therefore, overall results demonstrated that our nano-sized metabolic precursors could be extensively applied to new alternative tumor-targeting technique for molecular imaging and drug delivery system, regardless of the phenotype of heterogeneous tumor cells. Graphical abstract: